Supernovae and solar cycles embedded in a Dome F ice core - Motizuki, Yuko; Naka, Yoichi; Takahashi, Kazuya (Proceedings of the International Astronomical Union, 2009)
Abstract We have recently found signals of candidates for two historical supernovae and past solar cycles in a depth profile of nitrate ion concentrations in an ice core portion corresponding to the 10th and the 11th centuries. This ice core was drilled in 2001 at Dome Fuji (Dome F) station in Antarctica. We briefly review our findings and discuss why Dome F is appropriate for this study.